Perturbation theory of superconducting micronetworks. Second order and self-induction effects - Castro, José Ignacio; López, Arturo (Comisión Nacional de Energía Atómica; Argentina)
Fil: Castro, José Ignacio Comisión Nacional de Energía Atómica; Argentina